2022
DOI: 10.1021/acsami.2c07063
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Silver Nanowire Patterned Electrode on Robust PEN Substrate Using Poly(2-hydroxyethyl methacrylate) Underlayer

Abstract: Silver nanowire (AgNW) electrodes are among the most essential flexible transparent electrodes (FTEs) emerging as promising alternatives to brittle indium tin oxide (ITO) electrodes. The polymer comprising the plastic substrate to which the AgNWs are applied must also satisfy the mechanical requirements of the final device and withstand the device processing conditions. However, AgNW-based FTEs have some limitations, such as poor adhesion to coated plastic substrates, surface roughness, and difficulty in patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…, Table 1. Percolation exponents (n) and figures of merit (�) of the CS NF networks fabricated in this study and those of the nanostructured transparent conductors reported in previous studies 12,15,18,52,[54][55][56][57][58][59][60][61] . In comparison with those reported in earlier studies, the PVDF-Pt CS NF network prepared using the circular electrode collector exhibits an outstanding performance as a transparent conductor because of its large percolation figure of merit (� = 330.5) and small percolation exponent (n = 0.026).…”
Section: Resultssupporting
confidence: 53%
“…, Table 1. Percolation exponents (n) and figures of merit (�) of the CS NF networks fabricated in this study and those of the nanostructured transparent conductors reported in previous studies 12,15,18,52,[54][55][56][57][58][59][60][61] . In comparison with those reported in earlier studies, the PVDF-Pt CS NF network prepared using the circular electrode collector exhibits an outstanding performance as a transparent conductor because of its large percolation figure of merit (� = 330.5) and small percolation exponent (n = 0.026).…”
Section: Resultssupporting
confidence: 53%
“…In comparison, the Ag NW FTEs on x-PVCn coated PET showed good homogeneity with a sheet resistance of 29.5 ± 7.2 Ω sq −1 . Kwon et al 123 prepared high-performance Ag NW FTEs on a surface treated PEN substrate using poly(2-hydroxyethyl methacrylate) (PHEMA) as an underlayer. The contact angle of PEN was reduced from 84.2° to 46.5° after the surface coating of PHEMA, showing much better hydrophilic property, as shown in Fig.…”
Section: Engineering Strategies For Uniformity Improvementmentioning
confidence: 99%
“…321 In addition, surface modification of the substrate is also been considered to be one of the effective technology to improve the dispersion of NWs. 323 Introduction of poly(2-hydroxyethyl methacrylate) into the substrate enhances the adhesion between the substrate and AgNWs, improving the AgNW dispersibility. 323…”
Section: Intrinsically Stretchable Conductorsmentioning
confidence: 99%
“…323 Introduction of poly(2-hydroxyethyl methacrylate) into the substrate enhances the adhesion between the substrate and AgNWs, improving the AgNW dispersibility. 323…”
Section: Intrinsically Stretchable Conductorsmentioning
confidence: 99%